Functional and structural brain abnormalities in substance use disorder: A multimodal meta‐analysis of neuroimaging studies. (4th March 2023) - Yan, Hong; Xiao, Shu; Fu, Siying; Gong, Jiaying; Qi, Zhangzhang; Chen, Guanmao; Chen, Pan; Tang, Guixian; Su, Ting; Yang, Zibin; Wang, Ying
Abstract: Introduction: Numerous neuroimaging studies of resting‐state functional imaging and voxel‐based morphometry (VBM) have revealed that patients with substance use disorder (SUD) may present brain abnormalities, but their results were inconsistent. This multimodal neuroimaging meta‐analysis aimed to estimate common and specific alterations in SUD patients by combining information from all available studies of spontaneous functional activity and gray matter volume (GMV). Methods: A whole‐brain meta‐analysis on resting‐state functional imaging and VBM studies was conducted using the Seed‐based d Mapping with Permutation of Subject Images (SDM‐PSI) software, followed by multimodal overlapping to comprehensively investigate function and structure of the brain in SUD. Results: In this meta‐analysis, 39 independent studies with 47 datasets related to resting‐state functional brain activity (1444 SUD patients; 1446 healthy controls [HCs]) were included, as well as 77 studies with 89 datasets for GMV (3457 SUD patients; 3774 HCs). Patients with SUD showed the decreased resting‐state functional brain activity in the bilateral anterior cingulate cortex/medial prefrontal cortex (ACC/mPFC). For the VBM meta‐analysis, patients with SUD showed the reduced GMV in the bilateral ACC/mPFC, insula, thalamus extending to striatum, and left sensorimotor cortex. Conclusions: This multimodal meta‐analysis exhibited that SUD shows common impairment in both function and structure in the ACC/mPFC, suggesting that the deficits in functional and structural domains could be correlated together. In addition, a few regions exhibited only structural impairment in SUD, including the insula, thalamus, striatum, and sensorimotor areas.